Separation of samarium from medium rare earth mixture using multi-stage counter-current extraction - Nurul Ain, Ismail; Mohd Aizudin, Abd Aziz; Anwaruddin, Hisyam; Mohammad Alwi, Abidin (Taylor & Francis, 2020)
A large number of bifunctional ionic liquid extractant with ammonium-based have been formulated to separate and extract rare earth (RE) ions with better extraction efficiencies and selectivities compared to conventional extractant. In this paper, a methodical study for the separation of samarium from a mixture of samarium, europium, and gadolinium using bifunctional ionic liquid, [A336][P204] was developed. The optimum condition for the extraction was explored in regard to the concentration and type of acid as well as the organic to the aqueous ratio of the mixture. The sum of extraction and scrubbing stages are then calculated using the counter-current theory. The target purity and recovery ratio was set to 99.9% and 90%, respectively. Multi-stage of counter-current extraction process for three, four, and five stages were developed to simulate the extraction process. As a result, extraction with 3.0 M HNO3 and 4:1 organic to aqueous ratio selected as the best condition based on the value of separation factor, β: 2.81. The number of stages calculated by the theory matches the stages done experimentally, which is four. The outcome of the extraction indicates a high recovery value (>90%) but with a poor purity ratio (<70%). For scrubbing stages, by theory 13 stages is required, however in the experimental work, 18 stages needed to achieve the purity of >99%. The counter-current simulation of the samarium extraction from the mixed RE solution showed that a complete separation with excellent purity and recovery is possible and a process flow sheet has been presented.